Contribution of Chinese herbal medicine in the treatment of coronavirus disease 2019 (COVID‐19): A systematic review and meta‐analysis of randomized controlled trials. (16th November 2022) - Jin, Di; Wang, Jing; Xue, Jiaojiao; Zhao, Yunyun; Yan, Guanchi; Li, Xiangyan; Wang, Xiuge
Abstract: Coronavirus disease 2019 (COVID‐19) has become a global epidemic, and there is no specific treatment for anti‐COVID‐19 drugs. However, treatment of COVID‐19 using Chinese herbal medicine (CHM) has been widely practiced in China. PubMed, Embase, Cochrane Library, CNKI, Wanfang and VIP databases were searched to evaluate the efficacy and safety of CHM in the treatment of COVID‐19. Twenty‐six studies were included in this meta‐analysis. The included cases were all patients diagnosed with COVID‐19 according to the "New Coronary Virus Pneumonia Diagnosis and Treatment Program, " with a total of 2, 407 cases. Patients were treated with CHM, including 36 prescriptions, and 105 flavors of CHM were included. The results of the meta‐analysis showed that the CHM group improved in lung CT, clinical cure rate, clinical symptom score and time to negative for viral nucleic acid. However, this study still has many limitations due to the limited number of included studies. Therefore, high‐quality RCT studies are needed to provide more reliable evidence for CHM treatment of COVID‐19. In conclusion, CHM may significantly improve the clinical manifestations and laboratory indicators of patients with COVID‐19. In addition, no serious adverse reactions were found after CHM treatment. Therefore, CHM may be used as a potential candidate for COVID‐19. Highlights: COVID‐19 has become a global epidemic, and there is no specific treatment for anti‐COVID‐19 drugs. CHM has made a new breakthrough in the treatment of COVID‐19. CHM may relieve lung CT images of COVID‐19 patients. CHM may improve clinical symptoms of COVID‐19 patients. CHM may inhibit the expression of inflammatory factors in patients with COVID‐19.